Quantification of palladium in wastewater samples by matrix-matching calibration strategy assisted deep eutectic solvent based microextraction - Kocoglu, Elif Seda; Yilmaz, Ozge; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (SPRINGER, 2021)
An efficient, sensitive, and easy deep eutectic solvent based (DESb) liquid phase microextraction (LPME) method was developed to preconcentrate palladium for quantification at trace level by a flame atomic absorption spectrometry (FAAS) system, equipped with a lab made slotted quartz tube (SQT). All parameters of the DESb-LPME-SQT-FAAS system were optimized to lower the detection limit of the system. Using the optimized conditions, quantification and detection limits were obtained as 24.7 and 7.4 mu g L-1, respectively, which are compatible with the literature findings. Detection power of the FAAS system was enhanced by almost 50-fold using the optimum method based on LOD comparison. Recovery experiments were also performed with spiked wastewater matrix to examine the applicability/validity of the proposed method. The % recovery results were calculated between 85 and 91%. This established that the applicability of the developed method is high, and determination of this element in complex matrix can be performed accurately using the developed method.
Keywords: Palladium; SQT; FAAS; Deep eutectic solvent; Wastewater; LIQUID-LIQUID MICROEXTRACTION; ATOMIC-ABSORPTION-SPECTROMETRY; ENVIRONMENTAL-SAMPLES; PHASE MICROEXTRACTION; PRECONCENTRATION; EXTRACTION; SEPARATION; Environmental Sciences & Ecology